Effects of universal masking on Massachusetts healthcare workers' COVID-19 incidence - Lan, Fan Yun; Christophi, Costas A.; Buley, Jane; Iliaki, Eirini F.; Bruno-Murtha, Lou Ann; Sayah, Assaad J.; Kales, Stefanos N. (My University, 2020)
Background: Healthcare workers (HCWs) and other essential workers are at risk of occupational infection during the COVID-19 pandemic. Several infection control strategies have been implemented. Evidence shows that universal masking can mitigate COVID-19 infection, though existing research is limited by secular trend bias. Aims: To investigate the effect of hospital universal masking on COVID-19 incidence among HCWs compared to the general population. Methods: We compared the 7-day average incidence rates between a Massachusetts (USA) healthcare system and Massachusetts residents statewide. The study period was from 17 March (the date of first incident case in the healthcare system) to 6 May (the date Massachusetts implemented public masking). The healthcare system implemented universal masking on 26 March, we allotted a 5-day lag for effect onset and peak COVID-19 incidence in Massachusetts was 20 April. Thus, we categorized 17-31 March as the pre-intervention phase, 1-20 April the intervention phase and 21 April to 6 May the epidemic decline phase. Temporal incidence trends (i.e. 7-day average slopes) were compared using standardized coefficients from linear regression models. Results: The standardized coefficients were similar between the healthcare system and the state in both the pre-intervention and epidemic decline phases. During the intervention phase, the healthcare system's epidemic slope became negative (standardized β:-0.68, 95% CI:-1.06 to-0.31), while Massachusetts' slope remained positive (standardized β: 0.99, 95% CI: 0.94 to 1.05). Conclusions: Universal masking was associated with a decreasing COVID-19 incidence trend among HCWs, while the infection rate continued to rise in the surrounding community.
Keywords: Hospital; SARS-CoV-2; Infection control; Infectious disease; Personal protective equipment